Study of antioxidant activity of An Giang and Nghe An medicinal plants - Phan, Thị Anh Đào; Nguyễn , Xuân Hải; Nguyễn , Trung Nhân; Trần , Lê Quan; Nguyễn , Thị Thanh Mai (Journal of Technical Education Science, 2013)
36 extracts prepared from 36 medicinal plants from An Giang province and Nghe An province were studied on antioxidant activity by the DPPH radical scavenging test. Among of extracts, 25 showed an inhibition rate over 50% at 100 µg/ml; 15 had greater than 50% inhibition at 50 µg/ ml; six showed over 50% inhibition at 25 µg/ml. Five MeOH extracts exhibited strong DPPH inhibitory activity with possessing more than 50% inhibition at 10 µg/ml. The IC50 values of these extracts were found to be decreasing in the order: Raphidophora aurea (2.0 µg/ml) > Punica granatum (2.3 µg/ml) > Borassus flabellifer (4.9 µg/ml) > Gossampinus (8.8 µg/ml) > Nauclea orientalis (9.4 µg/ml). The results indicate a number of medicinal plants that may be useful for the treatment of diseases relating free radical damages, and provide the basis for further investigation on these medicinal plants.